2007
DOI: 10.1192/bjp.bp.106.026112
|View full text |Cite
|
Sign up to set email alerts
|

Heroin-assisted treatment for opioid dependence

Abstract: Heroin-assisted treatment is more effective for people with opioid dependence who continue intravenous heroin while on methadone maintenance or who are not enrolled in treatment. Despite a higher risk, it should be considered for treatment resistance under medical supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
169
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 238 publications
(184 citation statements)
references
References 17 publications
12
169
0
3
Order By: Relevance
“…Therefore, the use of BZD not prescribed in the trial was considered illicit BZD use. Further details on randomization, treatment and outcome were published previously (Haasen et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the use of BZD not prescribed in the trial was considered illicit BZD use. Further details on randomization, treatment and outcome were published previously (Haasen et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Psychopathology was assessed with the Global Severity Index (GSI) of the Symptom Checklist-90-Revised (SCL-90-R, Derogatis, 1994), with a special focus in this study on the anxiety and phobic anxiety subscales assessed at baseline, 1, 3, 6 and 12 months of treatment. The same two primary outcome measures (POM) as in the overall study (Haasen et al, 2007) were used, namely improvement of health and reduction of illicit drug use. For the POM on health, study participants were considered responders if they showed at least 20% improvement in the Opiate Treatment Index health scale (physical health) and/or at least 20% improvement in the GSI (mental health), without a deterioration of more than 20% in the other area of health.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As main outcomes, the study measured changes in health status and illicit heroin use, and found significant improvements in both as well as significantly higher retention rates for the experimental HAT groups (health outcome OR=1.41, 95% CI 1.05-1.89; illicit drug use OR=1.85, 95% CI 1.43-2.40; and retention rate 67 and 40% HAT/MMT, respectively). 21 The study furthermore found no difference on treatment outcomes between the two psychosocial (case management with integrated motivational interviews vs. psychoeducation in addition to drug counseling) interventions examined. In addition, a cost-benefit analysis found that HAT produced a net savings balance ("5,966) per patient per year, whereas the costs of MMT remained greater than its calculated savings (minus "2,069) because of its inability to substantially reduce crime and criminal justice system costs.…”
Section: Germanymentioning
confidence: 81%
“…33,41 Second, the discussed studies above have demonstrated in several different contexts that the implementation of HAT is feasible, effective, and safe as a therapeutic intervention. 21,24,26,30 This should not be seen as a conclusion that could be taken for granted because many observers expected disastrous consequences from the provision of medical heroin prescription.…”
Section: Discussionmentioning
confidence: 99%